2004
DOI: 10.1182/blood-2003-05-1406
|View full text |Cite
|
Sign up to set email alerts
|

BEAM-alemtuzumab reduced-intensity allogeneic stem cell transplantation for lymphoproliferative diseases: GVHD, toxicity, and survival in 65 patients

Abstract: We report the outcomes of reduced-intensity allogeneic stem cell transplantation using BEAM-alemtuzumab conditioning (carmustine, etoposide, cytosine arabinoside, melphalan, and alemtuzumab 10 mg/d on days ؊5 to ؊1) in 6 United Kingdom transplant centers. Sixty-five patients with lymphoproliferative diseases underwent sibling (n ‫؍‬ 57) or matched unrelated donor (n ‫؍‬ 8) transplantation. Sustained donor engraftment occurred in 60 (97%) of 62 patients. Of the 56 patients undergoing chimerism studies, 35 (63%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
134
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(148 citation statements)
references
References 25 publications
10
134
4
Order By: Relevance
“…14 Subsequent studies showed that FL has the most favorable outcome among lymphoprolyferative disorders. [15][16][17] In a cohort of patients enrolled in a multicenter Italian trial, the 3-year overall survival of patients with FL was 69%, similar to the survival rate reported by Vigouroux et al in this issue of the journal. 18 The optimal conditioning regimen has not been defined yet: fludarabine-based chemotherapy seems suitable because it combines both immunosuppression and anti-tumor activity.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…14 Subsequent studies showed that FL has the most favorable outcome among lymphoprolyferative disorders. [15][16][17] In a cohort of patients enrolled in a multicenter Italian trial, the 3-year overall survival of patients with FL was 69%, similar to the survival rate reported by Vigouroux et al in this issue of the journal. 18 The optimal conditioning regimen has not been defined yet: fludarabine-based chemotherapy seems suitable because it combines both immunosuppression and anti-tumor activity.…”
supporting
confidence: 79%
“…Alemtuzumab has been used as an in vivo T-cell depleting agent in several conditioning regimens. 16,17 So far, published data have shown that patients with similarly treated low-grade non-Hodgkin's lymphoma undergoing T-cell depleted transplants have (compared to similarly treated patients with aggressive non-Hodgkin's lymphoma) a superior event-free survival and a lower relapse rate compared to patients with aggressive histologies. 15 16 This observation is in contrast with the data published in this issue showing that patients in CR and PR had similar outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several mAbs that predominantly act by ADCC and CDC have been approved for the treatment of cancer patients. These include chimaeric IgG1 mAb rituximab (Rituxan s ) binding to the B-cell differentiation antigen CD20 for the treatment of Bcell lymphomas (Grillo-Lopez et al, 1999;Smith, 2003), humanised IgG1 mAb trastuzumab (Herceptin s ) targeting HER-2 (human epithelial growth factor receptor type 2) overexpressed in a subgroup of breast cancers (Vogel et al, 2001), humanised IgG1 alemtuzumab (Campath s ) targeting the differentiation antigen CD52 for the treatment of B-cell chronic lymphocytic leukaemia (Hale et al, 1998;Kottaridis et al, 2000;Faulkner et al, 2004) and edrecolomab (Panorex s ), a murine IgG2a mAb targeting Ep-CAM (epithelial cell adhesion molecule), which gained temporary approval in Germany for the treatment of colorectal carcinoma (Riethmuller et al, 1994;Gruber et al, 1996;Schwartzberg, 2001;White et al, 2001). Several other mAbs are currently at advanced stages of clinical development.…”
mentioning
confidence: 99%
“…Patients over the age of 60 who were transplanted in transplant centres, which routinely utilised alemtuzumab-based RIC regimens including combinations of fludarabine and melphalan (Flu/Mel), 15 fludarabine and Bu (Flu/Bu), 16 BCNU, BEAM 17 and fludarabine and Cy (Flu/Cy) ( Table 1) 18 were studied. GVHD prophylaxis consisted of CYA (5 mg/kg) commenced pre-transplant and subsequently dose-adjusted to achieve therapeutic levels.…”
Section: Transplant Regimens and Gvhd Prophylaxismentioning
confidence: 99%